2012
DOI: 10.4236/aid.2012.23009
|View full text |Cite
|
Sign up to set email alerts
|

The Serological Survey for Human Cysticercosis Prevalence in Mbulu District, Tanzania

Abstract: Human cysticercosis, a zoonotic disease due to Taeniasolium, is of the highly debilitating and stigmatizing neglected tropical diseases due to epilepsy, ophthalmia and dermatological disorders in endemic developing countries. Tanzania is among the sub-Saharan African countries with an average prevalence of porcine cysticercosis 17.2% [1], which increases the risk of human cysticercosis infection. Studies on people with epilepsy in northern zone of Tanzania show a 16.2% [2] to be suffering from neurocysticercos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
1
24
1
2
Order By: Relevance
“…These prevalence rates of Ab to CC were similar to a 2.2% prevalence rate reported among healthy individuals in Kenya [50]. However, our estimate is much lower than that found in a study conducted at the same time in communities of the Mbulu district where a prevalence proportion of 16.3% was reported when using a commercially available Western blot test (LDBIO Diagnostics) [51]. When using data from all participants initially recruited, the prevalence of TSOL was highest in the Mbulu district (5.2%), and this was true among HIV+ and HIV– participants, but was still lower than that found by Mwang’onde et al [51].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These prevalence rates of Ab to CC were similar to a 2.2% prevalence rate reported among healthy individuals in Kenya [50]. However, our estimate is much lower than that found in a study conducted at the same time in communities of the Mbulu district where a prevalence proportion of 16.3% was reported when using a commercially available Western blot test (LDBIO Diagnostics) [51]. When using data from all participants initially recruited, the prevalence of TSOL was highest in the Mbulu district (5.2%), and this was true among HIV+ and HIV– participants, but was still lower than that found by Mwang’onde et al [51].…”
Section: Discussionsupporting
confidence: 81%
“…However, our estimate is much lower than that found in a study conducted at the same time in communities of the Mbulu district where a prevalence proportion of 16.3% was reported when using a commercially available Western blot test (LDBIO Diagnostics) [51]. When using data from all participants initially recruited, the prevalence of TSOL was highest in the Mbulu district (5.2%), and this was true among HIV+ and HIV– participants, but was still lower than that found by Mwang’onde et al [51]. Possible explanation for these differences are the use of a different diagnostic test for the detection of Ab, possible selection bias of participants as no details on sampling is provided by the authors of a previous study [51], and possible clustering of CC in certain villages within the Mbulu district which was already described by Ngowi at al.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The prevalence of 14.3% (n = 300) obtained in this study is high compared to those reported elsewhere; 9.6%, 2.4%, and 1.3% reported in Jos [11], Togo, and Benin, respectively [15], but closer to the 16.3% (n = 544) reported in Mbulu community, Tanzania [16]. Other studies using similar antibody detecting techniques have reported prevalence of 7.4% in South Africa and 20.5% in Mozambique [6].…”
Section: Discussionmentioning
confidence: 46%
“…When cysticercosis is diagnosed in oral tissues, serological and coprological tests and imaging exams are essential for the detection of systemic disease [15]. In the present case, the coprological examination, chest X-ray and cranial tomography were negative.…”
Section: Discussionmentioning
confidence: 80%